2018
DOI: 10.1155/2018/5124735
|View full text |Cite
|
Sign up to set email alerts
|

Syzygium jambos Displayed Antibacterial and Antibiotic‐Modulating Activities against Resistant Phenotypes

Abstract: The present study was designed to evaluate the antibacterial activities of methanol extracts of bark and leaves of Syzygium jambos, as well as their synergistic effects with selected antibiotics against drug-resistant Gram-positive and Gram-negative bacteria. The crude extracts were subjected to qualitative phytochemical screening; broth microdilution method was used for antibacterial assays. Phytochemical studies indicate that leaves and bark extracts contained polyphenols, anthraquinones, tannins, and steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…Leaf and bark extracts of the plant expressed up to 70% of antibiotic-modulating activity against S. aureus strains at MIC/ 2. Similar results were obtained in association with tetracycline, ciprofloxacin, and erythromycin against Gram-negative bacteria ,6,10,14,18,2,6,10,15,19, including strains of Escherichia coli (AG100ATet, AG102), Enterobacter aerogenes (EA27, EA289), Klebsiella pneumoniae (KP55, KP63), Providencia stuartii (PS299645, NEA16) and Pseudomonas aeruginosa (PA01, PA124) (Wamba et al, 2018). Likewise, S. jambos leaf extracts demonstrated potent antiviral effects on the virus involved in vesicular stomatitis and against different types of herpes simplex virus (Abad et al, 1997;Athikomkulchai et al, 2008).…”
Section: Antimicrobial Activitysupporting
confidence: 69%
See 1 more Smart Citation
“…Leaf and bark extracts of the plant expressed up to 70% of antibiotic-modulating activity against S. aureus strains at MIC/ 2. Similar results were obtained in association with tetracycline, ciprofloxacin, and erythromycin against Gram-negative bacteria ,6,10,14,18,2,6,10,15,19, including strains of Escherichia coli (AG100ATet, AG102), Enterobacter aerogenes (EA27, EA289), Klebsiella pneumoniae (KP55, KP63), Providencia stuartii (PS299645, NEA16) and Pseudomonas aeruginosa (PA01, PA124) (Wamba et al, 2018). Likewise, S. jambos leaf extracts demonstrated potent antiviral effects on the virus involved in vesicular stomatitis and against different types of herpes simplex virus (Abad et al, 1997;Athikomkulchai et al, 2008).…”
Section: Antimicrobial Activitysupporting
confidence: 69%
“…Microbial growth inhibition zones and percentages, as well as minimum inhibitory concentrations (MICs), demonstrated that S. jambos has potential as a significant antibacterial agent. Wamba et al (2018) reported the capacity of S. jambos extracts to increase the potency of chloramphenicol antibiotic towards bacteria strains expressing MDR phenotype (Wamba et al, 2018). Leaf and bark extracts of the plant expressed up to 70% of antibiotic-modulating activity against S. aureus strains at MIC/ 2.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…To respond to the current challenges of discovering novel antibiotics, it is important to direct research towards new substances. In accordance with this, previous studies have shown that plants are sources of antimicrobial substances and therefore could be as an alternative to fight against infections due to MDR bacteria [4,[9][10][11][12][13][14][15][16].…”
Section: Introductionsupporting
confidence: 64%
“…The diversity of endophytic fungi from S. jambos and other species of the genus Syzygium is shown in Table 6. The potential of S. jambos bark extract has been known to have antibacterial activity against Staphylococcus aureus, Escherichia coli, Salmonella typhi, Bacillus subtilis (Murugan et al 2011;Begum et al 2015;Wamba et al 2018), and Propionibacterium acnes (Sharma et al 2013b). It has been reported that chemical compounds from the bark extract of S. jambos contain polyphenols, anthraquinones, tannins, triterpenes, steroids, saponins (Wamba et al 2018), pentacyclic triterpene, sitosterol, triterpene derivative 3-nor-2,3-fridelan (Haque et al 2015), jambosine alkaloids, pedunculagin ellagitannins, casuarinin, tellimagrandin I, strictinin, casuarictin, 2,3-HHDP glucose, and tellimagrandin II (Baliga et al 2017).…”
Section: Discussionmentioning
confidence: 99%